Active and reactive power control during unbalanced grid voltage in PV systems - Hunter, Gustavo; Andrade Aguero, Ivan Eric; Riedemann, Javier; Blasco-Gimenez, Ramón; Peña, Rubén (My University, 2016)
This paper presents a control strategy for a grid connected photovoltaic (PV) system aiming to regulate the active and reactive power injected to the electric system during asymmetrical voltage faults. The active power reference is obtained from a Maximum Power Point Tracking (MPPT) algorithm. The proposed control strategy generates the required reference currents to be imposed by the grid-tied inverter from the desired active and reactive power and the measured supply voltage. The scheme is validated for a single stage PV system where the inverter currents are regulated via predictive control. Results showing the performance of the strategy are presented during unbalanced voltage sags and swells.
Keywords: current control; low-voltage ride through (lvrt); mppt; power generation control; solar power generation; voltage unbalance